Social Justice and the University
XIII, 356 p.
Keywords: Can universities continue to play a major role in advancing social justice today? This volume illuminates key aspects of social justice as a theoretical project and as a set of practical challenges. Authors address related issues from the perspectives of active practitioners in the context of or from close proximity to universities.